Seismic Modeling and Imaging Using Wave Theory for Fault and Fracture Identification - Bashir Yasir, Deva Prasad Ghosh, Seyed Yaser Moussavi Alashloo, , . (2016)
Illumination of discrete transmissivity structures such as faults or fracture zones prior to exploration offers substantial benefits for all phases of field development. We have established a new way of seismic imaging through diffractions study using reflection seismology. A subsurface geological model is developed for highly productive field located in southern part of Malay Basin.